SDHB exon 1 deletion: A recurrent germline mutation in Colombian patients with pheochromocytomas and paragangliomas - Manotas, María Carolina; Rivera, Ana Lucía; Gómez, Ana Milena; Abisambra, Patricia; Guevara, Gonzalo; Medina, Vilma; Tapiero, Sandra; Huertas, Antonio; Riaño-Moreno, Julián; Mejía, Juan Carlos; Gonzalez-Clavijo, Angélica María; Tapiero-García, Mireya; et al. (Frontiers in Genetics, 2023)
Pheochromocytomas (PCCs) and paragangliomas (PGLs) (known as PPGL in combination) are rare neuroendocrine tumors of the adrenal medulla and extra-adrenal ganglia. About 40% of the patients with PPGL have a hereditary predisposition. Here we present a case-series of 19 unrelated Colombian patients with a clinical diagnosis of PPGL tumors that underwent germline genetic testing as part of the Hereditary Cancer Program developed at the Instituto Nacional de Cancerología, Colombia (INC-C), the largest reference cancer center in the country. Ten of 19 patients (52.63%) were identified as carriers of a pathogenic/likely pathogenic (P/LP) germline variant in a known susceptibility gene. The majority of the P/LP variants were in the SDHB gene (9/10): one corresponded to a nonsense variant c.268C>T (p.Arg90*) and eight cases were found to be carriers of a recurrent CNV consisting of a large deletion of one copy of exon 1, explaining 42% (8/19) of all the affected cases. Only one additional case was found to be a carrier of a missense mutation in the VHL gene: c.355T>C (p.Phe119Leu). Our study highlights the major role of SDHB in Colombian patients with a clinical diagnosis of PGL/PCC tumors and supports the recommendation of including the analysis of large deletions/duplications of the SDHB gene as part of the genetic counselling to improve the detection rate of hereditary cases and their clinical care.